(untitled) (Kriminalističke teme, 2003)
Authors analyze contents of the media from Bosnia and Herzegovina that are connected with processing of the actual cases of “ organized terrorism” in the post Dayton framework, that happened after the terrorist attack at the 11 September 2001.in the U.S.A. Using the methodological framework of the analyze of contents, authors emphasize necessity of professionalism in the presentation and perceptions of this very sensitive phenomenon of terrorism. Participating at this scientific conference as group of authors and using well known Journalistic methods, authors show tendency that analyze and the research become complex project of the Faculty in the security studies.